SAT0303 Clinical differences between definite and probable antiphospholipid (APS) patients: should they be treated the same?. (15th June 2017) - Signorelli, F; Balbi, G; Levy, RA
Abstract : Background: The management of patients with recurrent thromboses/pregnancy morbidity and transient detection of antiphospholipids antibodies (aPL) can be a medical challenge. Although these patients are commonly seen in practice, there are no specific guidelines for the treatment in this situations. Objectives: To investigate the clinical differences between definite and probable APS patients. Methods: We performed a cross-sectional study in a group of 90 outpatients seen in our department. Seventy-seven of them met the Sydney classficiation criteria for definte APS, and thirteen had thrombosis or gestational morbidity, but no definite serological criteria for the diagnosis of APS. Clinical and serological features were collected during visits and by chart review, and the two groups were compared. Transient aPL was defined as only one detection of aPL (lupus anticoagulant, anticardiolipin IgM/IgG and/or anti-beta-2-glycoprotein 1 IgM/IgG) after 2 or more assays, at least 12 weeks apart. Results: Demographic and clinical characteristics are shown in Table 1 . In a bivariate analysis, there was no difference between groups regarding the criteria and non-criteria manifestations of APS, except for the presence of livedo (p=0.033). In a multivariate regression analysis, the model was adjusted to age, sex, and variables with p<0.10 in the bivariate analysis (age, sex, race, livedo, Raynaud's phenomenon). No difference between groups was found after the analysis. Conclusions: This study suggests patients with transient detection of aPL have the same clinical characteristics of patients with definite APS, including thrombotic features, pregnancy morbidity, and non-criteria manifestations. In this context, our data suggests that both groups should be treated according to the current treatment guidelines for APS. Disclosure of Interest: None declared